(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this research paper, we have applied Homotopy Analysis Approach to the “time fractional nonlinear Schrodinger equation” to find its analytical periodic and solitary wave solution. Presence of convergence control parameter in this method guarantee the solution of time fractional differential equation in the form of rapidly convergent series. Obtained analytical solution has been compared and found in good agreement. This work demonstrates reliability and potential of HAM to study the time fractional partial differential equation